Gene expression dynamics after murine pancreatitis unveils novel roles for Hnf1α in acinar cell homeostasis. Issue 8 (23rd September 2011) - Molero, Xavier; Vaquero, Eva Cristina; Flández, Marta; González, Ana María; Ortiz, Maria Ángels; Cibrián-Uhalte, Elena; Servitja, Joan-Marc; Merlos, Anna; Juanpere, Núria; Massumi, Mohammad; Skoudy, Anouchka; MacDonald, Raymond; et al.
Abstract : Objectives: During pancreatitis, specific transcriptional programmes govern functional regeneration after injury. The objective of this study was to analyse the dynamic regulation of pancreatic genes and the role of transcriptional regulators during recovery from pancreatitis. Design: Wild-type and genetically modified mice (Hnf1α −/− and Ptf1a +/− ) were used. After caerulein or l -arginine induced pancreatitis, blood or pancreata were processed for enzymatic assays, ELISA, histology, immunohistochemistry, western blotting and quantitative reverse transcriptase-PCR. Nr5a2 promoter reporter and chromatin immunoprecipitation assays for Hnf1α were also performed. Results: After caerulein pancreatic injury, expression of acinar and endocrine genes rapidly decreased, but eventually recovered, depicting distinct cell-type-specific patterns. Pdx1 and Hnf1α mRNAs underwent marked downregulation, matching endocrine/exocrine gene expression profiles. Ptf1a, Pdx1 and Hnf1α protein levels were also reduced and recovered gradually. These changes were associated with transient impairment of exocrine and endocrine function, including abnormal glucose tolerance. On l -arginine pancreatitis, changes in Ptf1a, Pdx1 and Hnf1α gene and protein expression were recapitulated. Reduced Hnf1α and Ptf1a levels after pancreatitis coincided with increased acinar cell proliferation, both in Hnf1α −/− and Ptf1a +/− mice. Moreover, Hnf1α −/− mice had reduced Ptf1a protein as well as transcripts for Ptf1a and digestive enzymes. Dispersed acini from Hnf1α −/− mice showed suboptimal secretory responses to caerulein. Bioinformatics analysis did not support a role for Hnf1α as a direct regulator of digestive enzyme genes. Instead, it was found that Hnf1α binds to, and regulates, the promoter of Nr5a2, coding an orphan nuclear receptor that regulates acinar gene expression. Conclusions: Dynamic changes in gene expression occur on pancreatitis induction, determining altered exocrine and endocrine function. This analysis uncovers roles for Hnf1α in the regulation of acinar cell determination and function. This effect may be mediated, in part, through direct regulation of Nr5a2 .